The use of e-cigarettes and its risk of respiratory diseases - Al-Ghamdi, Hamed Saeed; Althagafi, Nader Ghazi; Alshawaf, Meshal Jamal; Allathiqani, Osama Mohammed; Almaflehi, Reem Abdulsalam; Almuzaini, Fahad Abdulrahman; Almohammadi, Munirah Salem; Alzahrani, Mazen Ibrahim; Alshakhs, Fatimah Mohammed; Wafa, Asala Mamdouh; Alajmi, Saleh Mubarak (International Journal Of Community Medicine And Public Health, 2021)
There are increasing concerns about the impact of using e-cigarettes on the overall health and respiratory complications of users. These modalities were proposed to potentially reduce the harmful events that are associated with cigarette smoking. Nevertheless, the acute and chronic effects secondary to the exposure and use of this modality are still controversial. However, it has been demonstrated that using the modality is associated with remarkable damage to lung injury because it releases significant amounts of reactive oxygen species, furans, volatile carbonyls, furans and metals (chromium, lead, and nickel). We have discussed the impact of e-cigarette using and exposure to its aerosol and the development and progression of the different respiratory diseases at the different clinical and pathological levels. Asthma, chronic bronchitis were the most significant lung conditions, and evidence indicated that exacerbation of symptoms was reported in some patients. Furthermore, acute exposure was also associated with the development of respiratory-related symptoms. Accordingly, studies indicated severe inflammatory reactions and significant lung injury were observed among e-cigarette users concerning vaping or exposure. Therefore, further preventive approaches are required by healthcare authorities to increase public awareness of the different hazards of using these modalities.